TINGKAT KESIAPSIAGAAN BENCANA GEMPA DAN TSUNAMI PADA MASYARAKAT GAMPONG MEUNASAH BALEE LAMPUUK KECAMATAN LHOKNGA KABUPATEN ACEH BESAR - Salwati, Henni; Desfandi, Mirza; Muliana, Aida (Universitas Syiah Kuala, 2024)
The Aceh region is an area prone to earthquakes, this is due to the geological and geographical conditions of Aceh which is at the confluence of three plates so it is very vulnerable to tektonic activity. In 2004 Aceh was rocked by an earthquake measuring 9.1 SR and was followed by a tsunami which claimed up to 173,741 lives. Mitigation activities are needed to reduce the risks arising from the earthquake and tsunami disaster. This research was conducted to determine earthquake and tsunami disaster preparedness in village communities using qualitative research methods. Data collection techniques were carried out using questionnaires through observation and interviews by asking questions to the community with a sample of 40 households taken randomly. Questions about disaster consist of 5 preparedness parameters, namely knowledge, policies or guidelines, emergency response plans, disaster warning systems, and resource mobilization. The result of the study showed that the preparedness of the village community for lighting customers in dealing with disasters was 97.5% and belonged to the very prepared category.